Sorting - Law, Karina; Crawford, Andy (London Franklin Watts, 2009)
"First non-fiction books introducing basic skills and concepts in a fun and engaging way. Simple questions encourage young children, from preschool age to early primary, to talk about their ideas and experiences. This title shows them how to sort."--Publisher's description
Arithmitic notions
1
Keywords: Set theory -- Pictorial works -- Juvenile literature; Set theory